Affection Reflected In The Notebook Novel (1996) By Nicholas Sparks: A Psychoanalytic Approach - Restuningtyas, Puspa Arum, Dr. Phil. Dewi Chandraningrum, M.Ed, Titis Setyabudi, S.S., M.Hum (2016)
The major problem of the study is showing affection and care to our beloved people that happened to the main character, Noah Calhoun. Noah is a stong, romantic and a man who really cares about other people, especially his wife. He never leaves his wife although she is affcted by Alzheimer's disease. The object of this study is to analyze Nicholas Sparks The Notebook nobel based on the structural elements and analyze this novel based on the psychoanalytic approach. The writer employs qualitative method. The researcher uses two data sources; primary and secondary. The primary data source is about the Notebook novel. Then the secondary data sources are the books about psychoanalysis, references from internet about The Notebook novel, and other sources, which have relation to the analysis. The method of data collection is library research and the techniques of data collection are reading the novel and note taking. Based on the analysis, the Researcer get some conclusions. This study shows that the problem faced by the major character is he loves his wife so much, he does everthing for Allie, including writing her letters for three years although the letters are never ever replayed by Allie; but after they meet for the first time, the love that has been lost over fourteen years grows back in their hearts. Until they grow old and Allie affected by Alzheimer's disease, Noah still beside her.